2010
DOI: 10.4025/actascianimsci.v32i3.8570
|View full text |Cite
|
Sign up to set email alerts
|

Fatores ambientais e de manejo sobre a composição química do leite em granjas leiteiras do Estado do Paraná, Brasil

Abstract: NRC-National Research Council. Nutrient requirements of dairy cattle. 7 th ed. Washington, D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
0
11
0
10
Order By: Relevance
“…These results are similar to those found by Borges et al (2009) in Western Santa Catarina. Fagan et al (2010) analyzed milk production throughout the seasons of the year, also found a significant difference (P<0.05) in milk protein content. In this study, the average protein content during summer, winter, and spring was 3.04%, while in the fall it was 2.87%.…”
Section: Resultsmentioning
confidence: 86%
“…These results are similar to those found by Borges et al (2009) in Western Santa Catarina. Fagan et al (2010) analyzed milk production throughout the seasons of the year, also found a significant difference (P<0.05) in milk protein content. In this study, the average protein content during summer, winter, and spring was 3.04%, while in the fall it was 2.87%.…”
Section: Resultsmentioning
confidence: 86%
“…Results suggest contamination is a consequence of animal feeding planning in the DPSs. Fagan et al (2010) found differences between DPSs (from 0,180 to 0,628 ppb), although their approach did not involve sampling, rather, a case study. In this study, it is possible to understand individual variations that were not noticed between dairy farmer groups, demonstrated by a coefficient of variation higher than 60%.…”
Section: Resultsmentioning
confidence: 99%
“…Food contamination is a current and thoroughly discussed issue, involving aspects such as public health (CALDAS; SOUZA, 2000) and animal production (FAGAN et al, 2010). Milk and dairy products have been given special attention, due to the increase in the demand of these products associated with the mounting concern for food safety (FAO, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As alterações nos constituintes do leite podem ter influencia de vários aspectos como manejo (Vallin et al, 2009); características genéticas (Deitos, Maggioni & Romero, 2010), etiologia (Oliveira et al, 2013), fase e ordem de lactação (Rossi et al, 2012), fatores ambientais (Fagan et al, 2010), raça e número de lactações (Reis et al, 2012). No presente estudo, a heterogeneidade do rebanho relacionados aos aspectos citados pode ter influencia a um desvio padrão alto e consequentemente, interferindo nos resultados.…”
Section: Cmt Gordura (%) Proteína (%) Lactose (%) Sólidos Totais (%) unclassified